An Incentive-based robust flexibility market for congestion management of an active distribution system to use the free capacity of Microgrids. (15th April 2023) - Babagheibi, Mahsa; Jadid, Shahram; Kazemi, Ahad
Highlights: Design an incentive-based LFM to integrate the flexibility services of MGs. Demand side energy management and rescheduling to use the free capacity of MGs. Use a modified ADMM method for LFM based on a request and response structure. Provide a RO model to consider the real-time price uncertainty in LFM. A two-stage model for LEM and LFM for congestion management of distribution system. Abstract: Microgrids (MG) formation has changed the passive structure of the distribution system. MGs participate in local energy markets as separate decision-making units to optimize their economic profit by energy trading with the distribution system operator. However, in the transition-duration from passive to active configuration, the lack of sufficient infrastructure may define new challenges for distribution system security. This paper proposes a robust model of a local flexibility market to incentivize the MGs to provide flexibility services to relieve line congestion. The proposed market model is, based on a request and response structure by adopting a modified ADMM method for flexibility services negotiations. The proposed flexibility market is considered a complementary market for bilateral energy trading of MGs and a distribution system for a fairer environment. The distributed market frameworks keep data privacy and a low computational burden for the market clearing process. The IEEE 33 bus test system with four connected MGs is considered to simulate the proposed model. For results validation, the social welfare function result is compared with the centralized problem structure, and the effects of flexibility market separation are analyzed with a comparison with a security constraints-based market design.